DINAMIKA POLITIK DI DALAM TATA KUASA LAHAN DI DESA TANJUNG MENANG KABUPATEN OGAN KOMERING ILIR - Dila, Nur Fhadilah; Yenrizal, Yenrizal; Zalpa, Yulion (Jurnal Studi Ilmu Politik, 2024)
The research is called "Political Dynamics in Land Tenure in Tanjung Menang Village, District. OIC", and the goal of this research is to find out the pattern of control and political dynamics in land administration in Tanjung Menang village, district. OIC. The research method used is qualitative, and the data collection technique used is by reading literature, which can be processed and collected from various data sources, such as books, articles, and interview reports.